The Electronic Portfolio: a Methodological Option - Zuñiga Benavides, José Francisco (2007)
The orientation of the academic work must be the integration of new methodology as strategy of the learning process, particularly when using the Electronic Portfolio. The schools which took parts in this implementation (as a trial) were the Escuela de Bibliotecología, Documentación e Información (Library Science School) and the Escuela de Literatura y Ciencias del Lenguaje (Literature and Language Science School) both of them from the Universidad Nacional de Costa Rica (National University of Costa Rica). Portfolio's main objective is to collect evidences from the student in which they demonstrates their own learning process and the professor’s role is analysis and evaluates the student’s progress.